2024
DOI: 10.1002/ajh.27184
|View full text |Cite
|
Sign up to set email alerts
|

Newly identified roles for PIEZO1 mechanosensor in controlling normal megakaryocyte development and in primary myelofibrosis

Vittorio Abbonante,
Anastasia Iris Karkempetzaki,
Catherine Leon
et al.

Abstract: Mechanisms through which mature megakaryocytes (Mks) and their progenitors sense the bone marrow extracellular matrix to promote lineage differentiation in health and disease are still partially understood. We found PIEZO1, a mechanosensitive cation channel, to be expressed in mouse and human Mks. Human mutations in PIEZO1 have been described to be associated with blood cell disorders. Yet, a role for PIEZO1 in megakaryopoiesis and proplatelet formation has never been investigated. Here, we show that activatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 64 publications
(145 reference statements)
0
2
0
Order By: Relevance
“…Shear stress is implicated in Piezo1 upregulation in various cell types such as in endothelial and vascular cells in the context of pulmonary hypertension [ 34 , 35 ], in endothelial cells via adrenomedullin [ 36 ] and in megakaryocytes (MKs) and platelets with the activation of integrins [ 37 ]. Stiffness sensation by Piezo1 was found to be associated with upregulation of the expression of the channel in MKs, as proven by culturing these cells in a 3D culture medium of different stiffness and by its enhanced MK expression in the case of primary myelofibrosis (PMF), a disease characterized by bone marrow fibrosis and augmented stiffness of the extracellular matrix (ECM) [ 38 ]. Stiffness created by kidney fibrosis was also shown to cause Piezo1 upregulation and to be associated with the progression of the disease [ 39 ].…”
Section: Overview Of Piezo1 Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Shear stress is implicated in Piezo1 upregulation in various cell types such as in endothelial and vascular cells in the context of pulmonary hypertension [ 34 , 35 ], in endothelial cells via adrenomedullin [ 36 ] and in megakaryocytes (MKs) and platelets with the activation of integrins [ 37 ]. Stiffness sensation by Piezo1 was found to be associated with upregulation of the expression of the channel in MKs, as proven by culturing these cells in a 3D culture medium of different stiffness and by its enhanced MK expression in the case of primary myelofibrosis (PMF), a disease characterized by bone marrow fibrosis and augmented stiffness of the extracellular matrix (ECM) [ 38 ]. Stiffness created by kidney fibrosis was also shown to cause Piezo1 upregulation and to be associated with the progression of the disease [ 39 ].…”
Section: Overview Of Piezo1 Propertiesmentioning
confidence: 99%
“…Moreover, the Piezo1 agonist Yoda-1 seemed to induce Ca 2+ influx by 170%, indicating that this channel is implicated in shear stress responses and Ca 2+ influx in human platelets and Meg-01 cells [ 37 ]. A recent study using primary bone marrow cells showed that Piezo1 acts as a brake for MK maturation and platelet production in vitro, as well as an attenuator of these processes in vivo in mice, as shown by the deletion of Piezo1/2 in the megakaryocytic lineage [ 38 ]. Elevated expression of the Piezo1 protein was observed in MKs isolated from the bone marrow of mice or patients affected by JAK2V617F-induced primary myelofibrosis, a clonal hematological neoplasia characterized by a stiff ECM in the bone marrow microenvironment [ 38 ].…”
Section: Piezo1 Function In Blood Cell Lineagesmentioning
confidence: 99%